ANALISIS KENYAMANAN TERMAL PADA BANGUNAN LITTLE TALK COFFEE BEKASI BERDASARKAN STANDAR GREEN BUILDING COUNCIL INDONESIA - Darryl Rizqi Maydian; Ayu Oktaviani (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2024)
Cafe is a place that provides foods and drinks, especially coffee. The Diffrences between a cafe and restaurant are the concept, atmosphere and type of food served. Cafes are designed with the aim of being a place to relax, discuss and even work for long hours, so user comfort needs to be considered that visitors can use the cafe comfortably. In this research, thermal or temperature is one of the factors that influences comfort in a building. Apart from that, with the Green Building Council Indonesia standard, it is hoped that the building will not only provide comfort to users, but also provide sustainability to the surrounding environment